Status and Use of Science Laboratories in the Secondary Schools of Sikkim - Sridevi, K.V. (JOURNAL OF INDIAN EDUCATION, 2019)
Science has always played an important role in understanding the natural phenomenon of the world. Thereby, scientific knowledge can become a characteristic of an individual by inculcating scientific temper at a young age, and for that, science practicum is an important aspect in the school curriculum. Science labs equipped with instruments, equipments and necessary glassware provides the conducive atmosphere for inculcation of science process skills. But the science labs at secondary stage lack all the elements which would have led to scientific temperament. This study reported the status and use of science labs in the secondary schools of Sikkim and highlighted the various policy implications which can go a long way in improving the condition of labs.